2023
DOI: 10.1021/acs.nanolett.3c01497
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Lignin Adhesion for High-Performance Bamboo Composites

Taotao Meng,
Yu Ding,
Yu Liu
et al.

Abstract: Bamboo composite is an attractive candidate for structural materials in applications such as construction, the automotive industry, and logistics. However, its development has been hindered due to the use of harmful petroleum-derived synthetic adhesives or low-bonding biobased adhesives. Herein, we report a novel bioadhesion strategy based on in situ lignin bonding that can process natural bamboo into a scalable and high-performance composite. In this process, lignin bonds the cellulose fibrils into a strong n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This process will cause the structure of biomass precursor to change during the process of removed impurity. For example, the use of strong alkali in the process of lipid rich biomass, long-term heating will make the chain of lignin and hemicellulose inside biomass material break, [66] thus affecting the their overall morphology and structure. Therefore, it is necessary to pay attention to the amount of sample and processing time when removing impurities, and the impact of different times will produce greater changes in appearance.…”
Section: Purified Components Of Plant-based Precursorsmentioning
confidence: 99%
“…This process will cause the structure of biomass precursor to change during the process of removed impurity. For example, the use of strong alkali in the process of lipid rich biomass, long-term heating will make the chain of lignin and hemicellulose inside biomass material break, [66] thus affecting the their overall morphology and structure. Therefore, it is necessary to pay attention to the amount of sample and processing time when removing impurities, and the impact of different times will produce greater changes in appearance.…”
Section: Purified Components Of Plant-based Precursorsmentioning
confidence: 99%
“…The assembly method and treatment processing affect the bonding performance of glued bamboo. Meng et al reported that an in situ glued-bamboo (glubam) composite demonstrated record-high shear strength of approximately 4.4 MPa and tensile strength of around 300 MPa [23]. The experimental flow chart and comparison of results are shown in Figure 2.…”
Section: Engineered Bamboo Building Materialsmentioning
confidence: 99%
“…Current wood adhesives employed in furniture, flooring, construction, and decoration predominantly originate from fossil-derived polymers, including formaldehyde-based adhesives and epoxy adhesives. Hazardous compounds including formaldehyde and phenol are continuously released during the production and use of aldehyde-based adhesives, endangering both people’s health and the environment. The depletion of oil resources and rising environmental concern have inspired researchers to seek eco-friendly and efficient alternatives from nature, which are green, renewable, and simple to process. Soybean meal (SM), an agricultural coproduct, offers the advantage of being abundant, inexpensive, and adaptable, showing great potential in panel manufacturing .…”
Section: Introductionmentioning
confidence: 99%